Sex-dependent temporal changes in astrocyte-vessel interactions following diffuse traumatic brain injury in rats - Sabetta, Zackary; Krishna, Gokul; Curry-Koski, Tala; Lopez, Mackenzie; Adelson, P. David; Thomas, Theresa Currier (Frontiers in Physiology, 2024)
Traumatic brain injury (TBI) is associated with diffuse axonal injury (DAI), a primary pathology linked to progressive neurodegeneration and neuroinflammation, including chronic astrogliosis, which influences longterm post-TBI recovery and morbidity. Sex-based differences in blood-brain barrier (BBB) permeability increases the risk of accelerated brain aging and early-onset neurodegeneration. However, few studies have evaluated chronic time course of astrocytic responses around cerebrovascular in the context of aging after TBI and sex dependence. We observed increased glial fibrillary acidic protein (GFAP)-labeled accessory processes branching near and connecting with GFAP-ensheathed cortical vessels, suggesting a critical nuance in astrocyte-vessel interactions after TBI. To quantify this observation, male and female Sprague Dawley rats (~3 months old, n=5-6/group) underwent either sham surgery or midline fluid percussion injury. Using immunohistochemical analysis, we quantified GFAP-labeled astrocyte primary and accessory processes that contacted GFAP-ensheathed vessels in the somatosensory barrel cortex at 7, 56, and 168 days post-injury (DPI). TBI significantly increased GFAP-positive primary processes at 7 DPI (P < 0.01) in both sexes. At 56 DPI, these vessel-process interactions remained significantly increased exclusively in males (P < 0.05). At 168 DPI, both sexes showed a significant reduction in vessel-process interactions compared to 7 DPI (P < 0.05); however, a modest but significant injury effect reemerged in females (P < 0.05). A similar sex-dependent pattern in the number of accessory processes provides novel evidence of long-term temporal changes in astrocytevessel interactions. TBI-induced changes in astrocyte-vessel interactions may indicate chronic BBB vulnerability and processes responsible for early onset vascular and neurodegenerative pathology.